Better yield from improved rust-resistant wheat - International Livestock Research Institute (International Livestock Research Institute, 2020)
Wheat is the most important food crop globally and is a principal source of nutrients in Ethiopia. For this reason, Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) program scientists believe that more research is needed to improve wheat yield in the country. This video highlights the work being done by Africa RISING and its partners to increase the productivity of wheat through research in rust-resistant and better-yielding varieties.